2012
DOI: 10.1111/j.1754-7121.2012.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Public sector performance and decentralization of decision rights

Abstract: In recent years, governments have introduced several reforms, often adopting management mechanisms traditionally associated with the private sector. This article looks specifically at the impact of decision‐rights decentralization, along with accountability mechanisms, on performance. Twenty public sector organizations, experiencing a shift from rule‐based to outcome‐based control mechanisms and benefiting from different levels of autonomy and decision margins, were studied. Results show a link between the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…Top-down command-and-control approaches tend to demoti vate public-service workers by failing to recognize their existing expertise and by considering them as obstacles to policy reform rather than partners in delivery. Empirical work analyzing 20 agencies operating with performance contracts in Quebec revealed that better outcomes arose when decision-authority and fi nancial controls were decentralized, not centralized (Aubert & Bourdeau, 2012), which is in keeping with Murekeysoni's (2017) comments on the adaptations of deliverol ogy in Ontario. In contrast to Murekeysoni's and Barber's own claims about the effectiveness of deliverology for Ontario's education reforms, Sattler (2012 ) found that these education-governance reforms were rooted in a neoliberal accountabili ty and performance reform agenda starting in 1990 that was implemented through a long-term, incremental, and "messy" process, with no evaluation of the ultimate impact on outcomes for students.…”
Section: What Are the Criticisms Of Deliverology And Its Consequencessupporting
confidence: 59%
“…Top-down command-and-control approaches tend to demoti vate public-service workers by failing to recognize their existing expertise and by considering them as obstacles to policy reform rather than partners in delivery. Empirical work analyzing 20 agencies operating with performance contracts in Quebec revealed that better outcomes arose when decision-authority and fi nancial controls were decentralized, not centralized (Aubert & Bourdeau, 2012), which is in keeping with Murekeysoni's (2017) comments on the adaptations of deliverol ogy in Ontario. In contrast to Murekeysoni's and Barber's own claims about the effectiveness of deliverology for Ontario's education reforms, Sattler (2012 ) found that these education-governance reforms were rooted in a neoliberal accountabili ty and performance reform agenda starting in 1990 that was implemented through a long-term, incremental, and "messy" process, with no evaluation of the ultimate impact on outcomes for students.…”
Section: What Are the Criticisms Of Deliverology And Its Consequencessupporting
confidence: 59%
“…What this means is that the performance and outcomes of organizations, both in the long and short terms, could be explained by the strategic choices they make. Public sector organizations often pursue multifaceted qualitative objectives which are sometimes conflicting and very difficult to measure, unlike private sector firms (Hawke, 2012;Aubert and Bourdeau, 2012;Boyne, 2003). To avoid some of these issues, this study adopts the "performance approach" based on agency theory in examining the impact of public sector organizational purchase decisions on their performance (Pestieau, 2009).…”
Section: Strategic Buying Decisions and Performancementioning
confidence: 99%
“…It has long been taken for granted by researchers that from the presence of performance data would come (better) informed decisions (for a recent review, see Aubert and Bourdeau ). As a result, “while the production of performance information has received considerable attention in the public sector performance measurement and management literature, actual use of this information has traditionally not been very high on the research agenda” (Van De Walle and Van Dooren : 2).…”
mentioning
confidence: 99%